2015
DOI: 10.5902/2179460x15922
|View full text |Cite
|
Sign up to set email alerts
|

Potencial Larvicida De Melia Azedarach L. E Ilex Paraguariensis St. Hil. No Controle De Aedes Aegypti (Linnaeus, 1762) (Diptera: Culicidae)

Abstract: Resumo O mosquito Aedes aegypti é o principal vetor da dengue. Os produtos sintéticos convencionais utilizados no controle populacional deste vetor têm apresentado resistência das populações, além de riscos à saúde da população e dos próprios aplicadores. Esse estudo se propôs a avaliar o potencial larvicida de extratos etanólicos de Ilex paraguariensis e Melia azedarach no controle de A. aegypti em condições de laboratório. Os ensaios foram conduzidos em recipientes plásticos com capacidade de 150 ml, onde fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 15 publications
0
20
0
1
Order By: Relevance
“…DUTRA, 2009). In the study of Busato et al (2015), in a bioassay using a hydroalcoholic extract of I. paraguariensis leaves, using the drying method in an oven for 48 hours, larvicide efficiency was checked on A. aegypti, with 100% mortality at a concentration of 2,000 μg/mL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DUTRA, 2009). In the study of Busato et al (2015), in a bioassay using a hydroalcoholic extract of I. paraguariensis leaves, using the drying method in an oven for 48 hours, larvicide efficiency was checked on A. aegypti, with 100% mortality at a concentration of 2,000 μg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown the effectiveness of natural products for the control of embryonic development, larval, pupa and adult emergence of A. aegypti (BRUNHEROT-TO & VENDRAMIM, 2001;ROSSI et al, 2007;BUSATO et al, 2015). A perspective arises from the study of Busato et al (2015) successfully testing the larvicide efficiency to the ethanol extracts of leaves of Ilex paraguariensis A. St.-Hill (Aquifoliaceae) on A. aegypti.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The insecticidal potential of this plant was tested by BUSATO et al (2015), who have reported a larvicidal efficiency on Aedes aegypti (Linnaeus, 1762), reaching 100% of mortality at the concentration of 2000μg ml -1 . Amongst the major metabolites reported in I. paraguariensis are alkaloids such as caffeine and theobromine (GNOATTO et al, 2007), which may be responsible for limiting the consumption of cabbage leaves by B. similaris.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing the results of Busato et al (2015), it is possible to infer that the extracts of the preparation method may have influenced the results for I. paraguariensis.…”
Section: Theezans Dried Leafmentioning
confidence: 99%